2021
DOI: 10.3390/insects12020125
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metarhizium robertsii on Adults of the Parasitoid Diachasmimorpha longicaudata and Parasitized Anastrepha ludens Larvae

Abstract: Biological control of the Mexican fruit fly, Anastrepha ludens, is mainly carried out by releasing parasitoids, such as Diachasmimorpha longicaudata, and by applying entomopathogenic fungi (EPF), such as Metarhizium anisopliae, Beauveria bassiana, or Isaria fumosorosea, which can be applied to the soil or dispersed using infective devices. The combined use of two or more biocontrol agents could improve A. ludens control, but IGP between natural enemies, if it occurs, may have negative effects. We evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…For example Nozad-Bonab et al [ 50 ] working on the same host used in this study, found that infecting Trichogramma brassicae Bezdenko (Hymenoptera: Trichogrammatidae) with M. anisopliae , reduced the longevity of the parasitoid. Similarly, in a study by Presa-Parra et al [ 51 ] the longevity of M. anisopliae infected Diachasmimorpha longicaudata Ashmead (Hymenoptera: Braconidae) was much shorter compared to their untreated counterparts. Dolichogenidea gelechiidivoris lays the highest number of eggs at one to three days after female emergence [ 20 ], when the parasitoid was infected with M. anisopliae ICIPE 20 due to the attraction to T. absoluta pheromone traps as found by Ayelo et al [ 52 ].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example Nozad-Bonab et al [ 50 ] working on the same host used in this study, found that infecting Trichogramma brassicae Bezdenko (Hymenoptera: Trichogrammatidae) with M. anisopliae , reduced the longevity of the parasitoid. Similarly, in a study by Presa-Parra et al [ 51 ] the longevity of M. anisopliae infected Diachasmimorpha longicaudata Ashmead (Hymenoptera: Braconidae) was much shorter compared to their untreated counterparts. Dolichogenidea gelechiidivoris lays the highest number of eggs at one to three days after female emergence [ 20 ], when the parasitoid was infected with M. anisopliae ICIPE 20 due to the attraction to T. absoluta pheromone traps as found by Ayelo et al [ 52 ].…”
Section: Discussionmentioning
confidence: 87%
“…Similarly Nozad-Bonab et al [ 50 ] reported 94–95% mortality of T. absoluta when T. brassicae was used in combination with M. anisopliae . In contrast, Presa-Parra et al [ 51 ] using the same fungus found that there was no difference in mortality of parasitised and non-parasitised Anastrepha ludens Loew (Diptera: Tephritidae) larvae sprayed with M. anisopliae .…”
Section: Discussionmentioning
confidence: 93%
“…We used Citavi software (version 6.11.0.0) to import the included studies. We extracted data on (1) pest, (2) control agents, (3) crop, (4) location, (5) study design, (6) evolution of pest and biocontrol agent populations, (7) crop damage, (8) crop yield, and (9) compatibility of biocontrol agents from the 49 selected articles [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Each combination of biocontrol agents was considered an experiment, leading to 1...…”
Section: Methodsmentioning
confidence: 99%
“…Metarhizium were also tested for compatibility with a braconid parasitoid Diachasmimorpha longicaudata (Ashmead) to control a tephritid fruit fly Anastrepha ludens Loew [ 13 ]. Metarhizium robertsii strain V3-160 and Metarhizium anisopliae strain MAAP1 caused moderate levels of mortality in D .…”
mentioning
confidence: 99%
“…longicaudata larvae developing inside treated hosts, A . ludens [ 13 ]. In another compatibility study, entomopathogenic fungi Beauveria bassiana (two strains) and trichogrammatid parasitoids in genus Trichogramma were evaluated for combined utilization against the European pepper moth Duponchelia fovealis (Zeller), family Crambidae [ 14 ].…”
mentioning
confidence: 99%